2014
DOI: 10.1007/s40258-014-0139-0
|View full text |Cite
|
Sign up to set email alerts
|

The geko™ Electro-Stimulation Device for Venous Thromboembolism Prophylaxis: A NICE Medical Technology Guidance

Abstract: The geko™ device is a single-use, battery-powered, neuromuscular electrostimulation device that aims to reduce the risk of venous thromboembolism (VTE). The National Institute for Health and Care Excellence (NICE) selected the geko™ device for evaluation, and invited the manufacturer, Firstkind Ltd, to submit clinical and economic evidence. King’s Technology Evaluation Centre, an External Assessment Centre (EAC) commissioned by the NICE, independently assessed the evidence submitted. The sponsor submitted evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…In addition, the use of compression stockings is contra-indicated in patients with leg oedema, cardiac failure, peripheral vascular insufficiency, and venous ulceration, which can limit their applicability, particularly in elderly populations who frequently have hip replacements procedures. Indeed, for patients where mechanical/pharmacological methods of prophylaxis are impractical or contraindicated, NICE medical technologies guidance recommend the adoption of NMES ( Summers et al., 2015 ) and this study further supports the NICE position. Incorrectly fitted compression stockings have also been associated with ischemia and increased risk of DVT and a recent study has found a significant increase in skin problems, including breaks, ulcers, blisters, and necrosis in patients who were fitted with compression stockings.…”
Section: Discussionsupporting
confidence: 67%
“…In addition, the use of compression stockings is contra-indicated in patients with leg oedema, cardiac failure, peripheral vascular insufficiency, and venous ulceration, which can limit their applicability, particularly in elderly populations who frequently have hip replacements procedures. Indeed, for patients where mechanical/pharmacological methods of prophylaxis are impractical or contraindicated, NICE medical technologies guidance recommend the adoption of NMES ( Summers et al., 2015 ) and this study further supports the NICE position. Incorrectly fitted compression stockings have also been associated with ischemia and increased risk of DVT and a recent study has found a significant increase in skin problems, including breaks, ulcers, blisters, and necrosis in patients who were fitted with compression stockings.…”
Section: Discussionsupporting
confidence: 67%
“…The causes of DVT are not clearly understood. Generally, Virchow’s triad (abnormalities in blood flow, blood constituents, and the vessel wall) is thought to be relevant 13 ) . To better understand blood flow during active ankle exercises, Sochart et al .…”
Section: Discussionmentioning
confidence: 99%
“…They are often used post-surgery to prevent deep vein thrombosis (DVT) (Goldhaber & Morrison, 2002), in procedures such as total hip replacement (Doran & White,1976); and have been found to reduce oedema in the thigh of total hip replacement patients post-surgery (Faghri et al, 1997). (Summers et al, 2015).…”
Section: Introductionmentioning
confidence: 99%